Prevalence and severity of acne in young people of Northern Italy. - Di Landro, A.; Marchesi, L.; Di Landro, G. (European Journal of Pediatric Dermatology, 2010)
Acne is a common skin condition which usually begins in adolescence and often resolves once early adulthood is reached. In international studies on the prevalence in schoolchildren, the frequency has varied from 30 to 100%. Data are not available for Italian young people. We studied in two steps a group of young students in a High School of Northern Italy; in the first step, after an educational session we administered a questionnaire about the presence of acne, its level of severity and therapy; in the second step, which was carried a year later in a different population of the same school, after the compilation of the same questionnaire, a physical examination was performed by a dermatologist. The disease was referred by 34% of students who compiled the questionnaire in the first study, while in the second study it was present in 39% by questionnaire and 43% in the physically examined group. Severe cases were present only in 2% of the population, all males. The 65.5% of the group with acne in the second study had never undergone a medical consultation. Our results with 43% of affected patients confirm other recent data from European countries and stress the importance of a correct information of young people frequently not so aware of the disease.